Feeding the fascination: crime-related tourism and the True Crime Museum - Thurston, Hannah (Critiquing violent crime in the media, 2021)
As tourists, when we visit any museum associated with prison or policing, when we seek out sites linked to infamous killings and killers, or when we tour a defunct jail cell, we are—in effect—consuming true crime narratives. Indeed, stories about ‘true’ crime continue to fascinate, titillate, and captivate tourists on a global scale. However, there is an inherent distortion involved within these spaces of non-fictional narrativity. Much like other mediated crime narratives, museums are no doubt partial and limited, forgetting as much as they remember, but this is unlikely to diminish their power or potency. This chapter then, will introduce the reader to some of the issues involved in crime-related tourism. Beginning with a typography of crime-related sites, it will then move on to examine the exhibits in one such site: the True Crime Museum in Hastings, England.